Autograft diameter in ACL reconstruction: size does matter - Alkhalaf Fahad N.A. (SICOT-J, 2021)
Background: Anterior cruciate ligament injuries are commonly seen in orthopedic surgery practice. Although anterior cruciate ligament reconstruction (ACLR) has come a long way, the causes of failure have yet to be fully understood. Objective: The aim of this study was to investigate whether or not the intraoperative 4-strand hamstring autograft diameter does in fact influence the failure rates of ACLR. Methods: Retrospective intraoperative data were collected from ACLR patients from the only tertiary center available in Kuwait. Patients who underwent ACLR from 2012 to 2018 for isolated ACL injuries were included in this study, allowing for a 24 month follow-up period The cohorts were categorized into 3 groups: patients with graft size≤8mm, 2, patients with graft sizes≥8mm with 4-strands and patients with graft sizes≥8mm with 4-strands or more. ANOVA analysis was applied to address group differences between mean graft size and strand numbers and subsequently the failure rates for each group. In addition, the Mann–Whitney U test was used to investigate the relationship between revision and initial ACL graft size. Results: Out of the 711 out of 782 patients were included in this study. Only 42.6% of the patients did not need more than 4-strands to achieve an 8mm sized autograft. The patients who had autografts≤8mm in this study accounted for 17.1% of the population. About 7.2% of these patients required revision surgery. Patients with a 4-strand autograft size that was less than 8mm were 7.2 times more at risk for ACLR failure (RR=7.2, 95% CI: 6.02; 8.35, p=0.007). Conclusions: There is a significant correlation between 4-strand autograft diameter size and the need for ACLR revision surgery. Level of evidence: IV case series